2017
DOI: 10.3329/jbau.v15i2.35073
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mastitis in dairy cows: somatic cell counts and associated bacteria in Mymensingh, Bangladesh

Abstract: Subclinical mastitis is an economically important disease of dairy cows and has a prominent place amongst the factors that limit milk production. This study was undertaken to determine the association of somatic cell counts (SCC) and occurrence of bacteria with SCM in smallholder dairy cows in Mymensingh, Bangladesh. A total number of 240 quarters milk samples from apparently healthy lactating cows were subjected to SCC using NucleoCounter ® SCC-100 ™ (Chemo Metec). A quarter was considered SCM positive if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
6
23
0
Order By: Relevance
“…Although the provision of SCC is readily available to most dairy farms in developed countries on a monthly basis through the dairy herd improvement (DHI) program, this practice yet not accustomed in Bangladesh. Because of the high prevalence (30-72%) of SCM and abundance of the mastitis pathogens [14][15][16][17][18][19], the provision of SCCs for routine SCM screening in dairy herds will be of great benefit in reducing the occurrence of SCM and ensuring milk quality as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although the provision of SCC is readily available to most dairy farms in developed countries on a monthly basis through the dairy herd improvement (DHI) program, this practice yet not accustomed in Bangladesh. Because of the high prevalence (30-72%) of SCM and abundance of the mastitis pathogens [14][15][16][17][18][19], the provision of SCCs for routine SCM screening in dairy herds will be of great benefit in reducing the occurrence of SCM and ensuring milk quality as well.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we found the CMT as an effective test kit for assessing SCM [13]. However, Sarker et al [23] and Sumon et al [17] found only 20.2% and 25% prevalence of SCM in dairy cows, respectively. A medium ranged prevalence of SCM (50.4% and 58%, respectively) was reported by Tripura et al [24] and Mpatswenumugabo et al [25].…”
Section: Resultsmentioning
confidence: 93%
“…Thus, prevention and control of mastitis is a big challenge throughout the world. Several researchers have reported the prevalence, potential risk factors, and comparison of different screening tests for bovine mastitis in Bangladesh [1017]. However, the screening tests of SCM using commercially available foreign kits need huge money.…”
Section: Introductionmentioning
confidence: 99%
“…Enterobacter spp has been reported from previous studies (Sumon et al, 2017) and are important agents of environmental intramammary infection and are mostly sourced from farm manure, bedding, and soil (Swartz and Christina, 2016).…”
Section: Discussionmentioning
confidence: 97%